Disparitas Pembatalan Peraturan Daerah Oleh Pemerintah Dan Kewenangan Judicial review Mahkamah Agung Perspektif Siyasah Dusturiyah - Hasibuan, Muhammad Azidan Rizky; Iwan, Iwan (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The unilateral repeal of Regional Regulations (Perda) by the central government following the enactment of Law No. 23 of 2014 has led to a conflict of authority with the Supreme Court’s judicial review function. Through Constitutional Court Decisions No. 137/PUU-XIII/2015 and No. 56/PUU-XIV/2016, the executive’s repressive oversight authority was officially revoked because it was deemed unconstitutional. This study aims to analyze this disparity in authority, examine the Constitutional Court’s legal reasoning, and explore the dynamics of this legal framework from the perspective of constitutional politics. The research method employed is normative law using the statutory approach, conceptual approach, case approach, and constitutional politics approach. Primary and secondary legal materials were analyzed qualitatively using a descriptive-analytical method. The results of the study indicate that the dualism of oversight between executive review and judicial review prior to the Constitutional Court’s decision was found to trigger legal uncertainty and undermine the independence of the judiciary. The Constitutional Court affirmed that the review of local regulations falls entirely within the constitutional jurisdiction of the Supreme Court. From a constitutional politics perspective, the transfer of authority to annul local regulations to the judicial branch (the Supreme Court) is deemed highly beneficial. This mechanism is consistent with the principles of justice (al-'adl), the public interest (al-maslahah), and checks and balances, and is capable of preventing the abuse of power by those in authority through an objective and independent judicial process